Attitude and performance in controlling dust particles from dental prosthesis and appliance adjustment: a survey of dentists and dental assistants - Nareudee Limpuangthip; Prarom Salimee; Phanomporn Vanichanon (Nature Publishing Group, 2024)
Abstract Objectives To assess the attitude and practices of dentists and dental assistants in managing dust particles generated during dental prostheses or appliances grinding and polishing. Materials and methods Data were collected from 207 dentists and 125 dental assistants through an online questionnaire. The questionnaire included adjusted prosthesis types, self-protective methods, types and frequency of protective device use, and reasons for non-frequent use. Results Protective grinding devices, including dust protective boxes and mounted plastic sheets, were commonly used for substantial acrylic resin adjustments, while air blowing was preferred for minor adjustments. Post-COVID-19, there was a 3-fold increase in the use of protective grinding devices among dentists and a 1.3-fold increase among dental assistants. During try-in procedures, dentists commonly rinsed prostheses with water rather than using disinfectants. Non-frequent users adopted self-protection methods, such as face shields and air filters. Surgical drapes and high-volume evacuators were used for patient's protection. Conclusion Despite an increased tendency of the use of protective grinding devices following COVID-19, a significant number still report infrequent use. Identified protective devices in this study have drawbacks not fully meeting dentists' expectations. Invention of a more user-friendly device is necessary to ensure regular use, preventing potential toxicity from dust particles.